2021
DOI: 10.1186/s12859-021-04519-4
|View full text |Cite
|
Sign up to set email alerts
|

pyKVFinder: an efficient and integrable Python package for biomolecular cavity detection and characterization in data science

Abstract: Background Biomolecular interactions that modulate biological processes occur mainly in cavities throughout the surface of biomolecular structures. In the data science era, structural biology has benefited from the increasing availability of biostructural data due to advances in structural determination and computational methods. In this scenario, data-intensive cavity analysis demands efficient scripting routines built on easily manipulated data structures. To fulfill this need, we developed p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 44 publications
1
24
0
Order By: Relevance
“…The algorithm pyKVFider 51 was used to map the predicted peptidoglycan-binding cavity and the amino acids that are in its vicinity (Fig. 7 E).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The algorithm pyKVFider 51 was used to map the predicted peptidoglycan-binding cavity and the amino acids that are in its vicinity (Fig. 7 E).…”
Section: Resultsmentioning
confidence: 99%
“…COACH is a meta-server approach that combines multiple function annotation results (ligand-binding sites) from the COFACTOR, TM-SITE and S-SITE programs 35 , 36 , 71 . The python package pyKVFider 51 was used to map the peptidoglycan-binding cavity and the amino acids that are in its vicinity. The structural analysis was performed using PyMOL 48 , UCSF Chimera 46 , PDBsum web server 47 , and LigPlot + v.2.2 55 .…”
Section: Methodsmentioning
confidence: 99%
“…In the Lili-Mip1 structure, we found that Phe-98 and Phe-100 have moved upwards, causing a decrease in the size of the ligand binding pocket (Figure 4A-D). To better understand how the ligand binding pocket size changes between structures, we quantitated the cavity volumes of different Lili-Mip using parKVfinder [46]. This is seen better in contrast with Lili-Mip2, where the Phe-98 and Phe-100 face downwards, increasing the cavity volume (Figure 4E-G).…”
Section: Resultsmentioning
confidence: 99%
“…However, KVFinder software, originally published in 2014, is deprecated, and the KVFinder project is currently composed of two independent software: Parallel KVFinder (parKVFinder) 21 and Python-C Parallel KVFinder (pyKVFinder). 15 parKVFinder is available with an easy-to-use PyMOL plugin with an intuitive graphical user interface that allows users to explore customizable parameters for cavity detection and characterization. On the other hand, pyKVFinder is available as a Python package with efficient scripting routines built on easy-to-handle data structures, facilitating complex structural data analysis.…”
Section: Cavity Characterization In Supramolecularmentioning
confidence: 99%
“…A comprehensive taxonomy of geometry-based cavity detection approaches includes grid-, probe-, tessellation-, and surface-based techniques and their combination . The technique employed to extract cavities from the molecular structure is mainly what differentiates them. Grid-based algorithms (e.g., POVME 3.0) represent a set of atoms as discrete points, usually using an axis-aligned 3D grid such as a scalar field, i.e., density map, where each discrete point is an integer or a boolean.…”
Section: Cavity Detection In Computational Chemistrymentioning
confidence: 99%